The feeling of patriotism is the highest value - Uzakov, Akram (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Homeland is the ground where you breathe first, the ground where you witness your first step, the corner where you witness your first laugh. You can continue this, there is no limit to it. In fact, all this is missing about the homeland. The homeland is, in fact, the place where our umbilical cord blood was shed, the corner of our ancestors. The homeland is a concept that embodies the human psyche, lifestyle, consciousness and thinking, past, present and future. The homeland begins at the threshold, the place where he was born and raised. That is why it is necessary for a child to grow up in the house where he lives and breathes, to have eternal love and devotion to the motherland, which is a magnificent and powerful place. Everyone’s love for the motherland is breast milk. the mother is absorbed in her body by the goddess and the love of the parents, the child who loves his parents, their ancestors, their traditions, customs, professions, loves others as well. He is proud of his nation, people, literature, art, religion and culture, inspired by the nature of the country where he grew up, and understands the value of its sacred land. That is why the love and devotion to the motherland, which is a magnificent and powerful place for a child to grow up in the house where he lives and breathes, is eternal